The Vascular Anatomical Basis for a Well-Designed Reconstruction of the Ala Nasi by a Microsurgical Preauricular Flap Technique - Gianpaolo Faini; Alice Ferrari; Lena Hirtler; Lorena Giugno; Sergio Arleo; Barbara Buffoli (Surgical Techniques Development)
Background: A microsurgical auricular flap represents a single-step technique for the reconstruction of full-thickness defects of the ala nasi. To achieve the best surgical outcomes, it is essential to have an exhaustive knowledge of the vascular network to improve the management of the surgical flap. This study aimed to provide an anatomical and surgical guide for a well-designed reconstruction of the ala nasi using a free preauricular flap. Methods: In this study, three fresh-frozen and two formalin-fixed human head specimens injected with red silicone rubber to enhance the arterial facial system were used. The reconstruction of the full-thickness defect of the ala nasi was performed using a microsurgical auricular flap technique, with the dimensions of the ala nasi and the preauricular flap duly noted. In addition, anatomical dissections were conducted, during which the positions and diameters of the main donor and recipient vessels were measured. Results: A presurgical evaluation was performed to define the flap design. A comparison of the shape and mean dimensions of the ala nasi defect (height 9.66 ± 1.40 mm; thickness 3.52 ± 0.53 mm) and the preauricular flap (height 8.50 ± 2.68 mm; thickness 3.92 ± 1.29 mm) indicated that this flap was an optimal option for the reconstruction of the ala nasi. The surgical procedure involved the full-thickness removal of the ala nasi, and the harvesting and insertion of the preauricular flap. The anatomical measurements demonstrated that the facial artery and veins were the optimal recipient vessels, with a diameter of >1 mm (2.08 ± 0.56 and 2.85 ± 0.74 mm), suitable for anastomosis with the superficial temporal artery and vein (1.86 ± 0.58 and 1.66 ± 0.15 mm). In addition, the postsurgical evaluations indicated a slight mean difference in the thickness (1.14 ± 0.65 mm) and height (1.68 ± 1.18 mm) between the ala nasi and helix and a satisfactory VAS score (7.9 ± 0.57). Conclusions: Our surgical and anatomical data provide compelling evidence in favour of free preauricular flap reconstructions of the ala nasi. This procedure allows for the correct choice of recipient vessels and the creation of a well-designed surgical flap.